2017
DOI: 10.1620/tjem.243.85
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applicability and Psychometric Properties of Manual Function Test for Patients with Stroke

Abstract: The Manual Function Test (MFT) is a tool to assess upper extremity motor impairment associated with stroke. This study investigated psychometric properties of the Korean version of the MFT and to establish normative data. Eighty-one patients were enrolled to evaluate MFT, Fugl-Meyer Assessment (FMA) and manual muscle test (MMT). MFT was completed by eight raters on two occasions separated by 6 weeks. Absolute and relative reliability and validity were examined. Additionally, MFT was assessed on 75 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In contrast, the functional independence measure motor score (FIM-M) is widely used as an assessment of disability, scored in more detail than the BI, and can evaluate the change in independence of ADL with acceptable floor/ceiling effects and a high inter-rater reliability (Ottenbacher et al, 1994; Sivan et al, 2011; Wei et al, 2011). Regarding the MFT, Kim et al (2017) reported that the relationship between the MFT and FMA-UL is still unclear, despite the fact that FMA-UL is a standard and common stroke-specific measurement tool for comprehensive evaluation of upper extremity function and has a high inter-rater reliability (Duncan et al, 1983; Michaelsen et al, 2011; Sanford et al, 1993). Therefore, a combination of the FMA-UL and FIM should be used to clarify the relationship between the motor function of the affected upper limb and ADL performance.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the functional independence measure motor score (FIM-M) is widely used as an assessment of disability, scored in more detail than the BI, and can evaluate the change in independence of ADL with acceptable floor/ceiling effects and a high inter-rater reliability (Ottenbacher et al, 1994; Sivan et al, 2011; Wei et al, 2011). Regarding the MFT, Kim et al (2017) reported that the relationship between the MFT and FMA-UL is still unclear, despite the fact that FMA-UL is a standard and common stroke-specific measurement tool for comprehensive evaluation of upper extremity function and has a high inter-rater reliability (Duncan et al, 1983; Michaelsen et al, 2011; Sanford et al, 1993). Therefore, a combination of the FMA-UL and FIM should be used to clarify the relationship between the motor function of the affected upper limb and ADL performance.…”
Section: Introductionmentioning
confidence: 99%